Pengaruh Media Audio Visual terhadap Pemahaman Maharoh Istima’ Bahasa Arab - Rahmawati, Novi (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
This article discusses the influence of audio visual media on maharoh istima 'is motivated by the views of the majority of students about the difficulty of learning Arabic. Learning success cannot be separated from the preparation of all parties. The teacher must be able to grow students' motivation to learn. This learning model requires students to be able to say mufrodat or sentences and train the courage to speak Arabic in front of their friends.The objectives of this study were: To explain the understanding of Maharoh istima’ ', as well as the learning tools, to find out the learning method of Maharoh istima’ using the Audio Visual method, to find Maharoh istima’s learning constraints using audio visual.The design of this study uses a quantitative approach with a type of correlational research. The population in this study were all students of class VIII MTs Persis 79 Rajapolah. Sampling in this study used nonprobability sampling technique with saturated sampling, namely sampling technique if all members of the population. So that in this study the sample used was all class VIII students. Data collection uses a test that serves to determine the value of learning outcomes in problem solving. With the following results. (1) there is the influence of audio-visual media on maharoh istima ', the results are obtained from a significance value of less than 0.05, a significance value of 0.000. Thus it can be concluded that there is a significant influence between audio visual media on students' maharoh istima.